From Chitosan to Chitin: Bio‐Inspired Thin Films for Passive Daytime Radiative Cooling. Issue 11 (15th February 2023) - Lauster, Tobias; Mauel, Anika; Herrmann, Kai; Veitengruber, Viktoria; Song, Qimeng; Senker, Jürgen; Retsch, Markus
Abstract: Passive radiative daytime cooling is an emerging technology contributing to carbon‐neutral heat management. Optically engineered materials with distinct absorption and emission properties in the solar and mid‐infrared range are at the heart of this technology. Owing to their low emissive power of about 100 W m −2 during daytime, substantial areas need to be covered with passive cooling materials or coatings to achieve a sizeable effect on global warming. Consequently, biocompatible materials are urgently needed to develop suitable coatings with no adverse environmental impact. It is shown how chitosan films with different thicknesses can be produced from slightly acidic aqueous solutions. The conversion to their insoluble form chitin in the solid state is demonstrated and the conversion is monitored with infrared (IR) and NMR spectroscopy. In combination with a reflective backing material, the films show below‐ambient temperature cooling capabilities with a suitable emissivity in the mid‐IR region and low solar absorption of 3.1–6.9%, depending on the film thickness. This work highlights the potential of chitosan and chitin as widely available biocompatible polymers for passive radiative cooling applications. Abstract : The potential of chitosan and chitin for the application as passive radiative cooling materials is investigated. A solid‐state reaction is used to convert chitosan to its insoluble form chitin. Based on extensive optical characterization, both biopolymers are capable of below ambient temperature passive cooling.